Evaluating Drug Interaction Risks: Nirmatrelvir & Ritonavir Combination (PAXLOVID®) with Concomitant Medications in Real-World Clinical Settings - Zatovkaňuková, Petra; Veselý, Dalibor; Slíva, Jiří (Pathogens (Basel, Switzerland), 2024)
BACKGROUND: This research article delves into the battle against the COVID-19 pandemic, focusing on the efficacy and, particularly, the safety of the combination of nirmatrelvir with ritonavir, which is found in the pharmaceutical product Paxlovid®. This study aims to analyze the potential interactions of commonly prescribed medicinal products with Paxlovid®, shedding light on its utilization in specific medical fields. METHODS: Prescription data from the Czech Republic's Institute of Health Information and Statistics (IHIS CR) was analyzed, covering 4 million COVID-19 patients and 87.5 million medication records from September 2019 to February 2022. This study focused on potential drug interactions with Paxlovid among the 50 most frequently prescribed medications, with particular attention to four specialties: general medicine, internal medicine, infectious diseases, and diabetology. RESULTS: In this study of the 50 most commonly prescribed drugs, 56% showed no interaction with Paxlovid, 30% had a potential for interaction, and 14% were not specifically mentioned in relation to Paxlovid, with no drugs found to be contraindicated overall. However, in specific medical fields, including diabetology, infectious diseases, internal medicine, and general medicine, certain drugs had potential interactions when co-administered with Paxlovid. CONCLUSIONS: Paxlovid remains a valuable option for early COVID-19 treatment but requires a careful consideration of potential drug interactions, especially in high-risk specialties. A thorough assessment of concurrent medications is essential to optimize safety and efficacy in patients receiving Paxlovid.
Keywords: Humans; nirmatrelvir; fixní kombinace léků; lékové interakce; lidé; Paxlovid; Drug Interactions; COVID-19; Ritonavir; antivirové látky; Czech Republic; farmakoterapie COVID-19; Antiviral Agents; ritonavir; Česká republika; SARS-CoV-2; Drug Combinations; drug interactions; COVID-19 Drug Treatment